Flexibility: Whose Choice Is It Anyway? - Zeytinoglu, Isik U.; Cooke, Gordon B.; Mann, Sara L. (Relations industrielles / Industrial Relations, 2009)
SummaryThis paper examines whether flexible work schedules in Canada are created by employers for business reasons or to assist their workers achieve work-life balance. We focus on long workweek, flextime, compressed workweek, variable workweek length and/or variable workweek schedule. In the last three decades, two streams of literature have emerged on flexibility. One stream of literature discusses flexibility as demand-driven, that is, a strategic initiative of employers to enhance the business requirements of the firm. The other stream of literature discusses flexibility as supply-driven, where employees have the ability to influence the decisions about the nature of their work schedules and where employees, especially women, demand flexible work schedules for work-life balance. Thus, we ask are flexible work schedules created for business reasons or to assist workers achieve work-life balance?Statistics Canada’s 2003 Workplace and Employee Survey data linking employee microdata to workplace (i.e., employer) microdata are used in the analysis. Results show that more than half of the workers covered in this data have at least one of the five specified types of flexible work schedules. Approximately 5% of workers have a long workweek, 36% have flextime, 7% a compressed workweek, 13% a variable workweek length, and 16% a variable workweek schedule. Only two in five Canadians have a standard work schedule. Employment status, unionized work, occupation, and sector are factors consistently associated with flexible work schedules. Personal characteristics of marital status, dependent children, and childcare use are not significantly associated with flexible work schedules, while females are less likely to have a flexible work schedule than males. Overall, results suggest that flexible work schedules are created for business reasons rather than individual worker interests. Thus, if public policy makers are committed to facilitating workers’ work-family-life balance interests, then our results suggest that separate policy initiatives designed specifically for workers will be required.